3D insights into the multiorigins of nanophase Fe 0 in the Moon surface - Yiheng Dai; Zezhou Li; Tianyi Jia; Zhiheng Xie; Ruimin Wang; Zongjun Yin; Bing Shen; Jihan Zhou (Proceedings of the National Academy of Sciences, 2026)
Nanophase metallic iron (npFe 0 ) in lunar soils is a key indicator for understanding the space weathering mechanisms of airless bodies. However, the detailed three-dimensional (3D) spatial topology and distribution of layered npFe 0 have rarely been documented in lunar soil samples. Here, we reveal the unique 3D spatial multilayered distributions and morphologies of npFe 0 in the Chang’e-5 impact glass using a combination of electron tomography and spectroscopic techniques, demonstrating that npFe 0 originates from multiple effects including iron sulfide decomposition, Fe(II) disproportionation, and solar wind irradiation. We provide direct evidence for the decomposition of iron sulfide to produce irregularly shaped npFe 0 . This study quantifies the 3D abundance of npFe 0 in a piece of lunar impact glass, revealing localized Fe 0 accumulation up to 7.1 wt%. Our results provide 3D nanoscale analysis for multiple coexisting formation mechanisms of npFe 0 , elucidating the complex space weathering processes in the lunar surface.